Developing Soft Skills of Students Through Multimodal Instruction by Pre-Service Educators in a State University - Renacido, John Marvin D.; Biray, Ersyl T. (Future Science / FSH-PH Publications, 2025)
Given the low ranking of Filipino children in reading, science, and mathematics at the latest 2022 Programme for International Student Assessment (PISA), and the lack of empirical evidence about multimodal instruction of teachers and the development of soft skills of students, this mixed methods study looked into the transformative impact of multimodal instruction on the development of soft skills of students such as communication, flexibility, and leadership. It will also track the influence of soft skills on student outcomes such as employability, academic success, and personal growth. Survey questionnaires were used to effectively assess and monitor the data given by the respondents and a five-point Likert Scale was utilized to establish a clear conclusion of the variables. Semi-structured interviews with open-ended questions were conducted to reassure the quantitative findings. Results of the descriptive statistics showed that all of the variables met the highest mean, strongly agreeing with statements from each variable and was further reinforced by the qualitative analysis from the respondents. Moreover, it was found out that pre-service teachers prefer to use videos and animations, as their main multimodal instruction, to illustrate complex concepts visually. Next is incorporating visual diagrams, mind influence maps, or conceptual maps, and third but not least, applying hands-on activities and experiments for tactile learners. Thus, it concludes that multimodal instruction paves the path for attaining soft skills and that soft skills highly influence student outcomes.